2011
DOI: 10.1353/hpu.2011.0071
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and Retention of Primary Care Physicians at Community Health Centers: A Survey of Massachusetts Physicians

Abstract: As the backbone of the safety-net system, community health centers (CHCs) provide access to essential services, yet contend with high provider turnover. Using an online survey, primary care physicians (PCPs) at 62 Massachusetts League of Community Health Centers member sites were queried about recruitment and retention factors. Nearly 300 (n=294) PCPs representing 46 CHCs completed the survey. Female physicians, those practicing in the greater Boston area, and those in practice for 10 or more years reported a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 16 publications
0
35
0
Order By: Relevance
“…14 Their findings were corroborated by Savageau et al 12 In Brazil, a previous study identified the following reasons for difficulty in hiring medical specialists, as pointed out by managers of municipal and state public healthcare systems: lack of graduate professionals, according to the criteria of the Ministry of Education and the Brazilian Medical Association; lack of professionals with the experience required for the work; and the fact that professionals consider that the remuneration levels offered by institutions are low. 15 Comparison between these data and the preliminary results from the present study showed that training more doctors does not lead to more specialists working in the public healthcare system.…”
Section: Employment Situation In June 2014mentioning
confidence: 77%
See 1 more Smart Citation
“…14 Their findings were corroborated by Savageau et al 12 In Brazil, a previous study identified the following reasons for difficulty in hiring medical specialists, as pointed out by managers of municipal and state public healthcare systems: lack of graduate professionals, according to the criteria of the Ministry of Education and the Brazilian Medical Association; lack of professionals with the experience required for the work; and the fact that professionals consider that the remuneration levels offered by institutions are low. 15 Comparison between these data and the preliminary results from the present study showed that training more doctors does not lead to more specialists working in the public healthcare system.…”
Section: Employment Situation In June 2014mentioning
confidence: 77%
“…9 One important question is how to attract doctors to work in primary care and in rural areas. No exact answers have been presented, but the following have been found to be predictive of continued retention in the face of adversity: revision of medical school curricula to encompass current inpatient-oriented training programs; 10 hiring of doctors with residency in family or community practice; 11,12 working in a greater city area; 12 satisfaction with community health centers; 12 and prior resilience under adverse circumstances. 13 Landry et al 14 observed that medical training at the undergraduate level did not affect the likelihood of ever or currently practicing in a Canadian province.…”
Section: Employment Situation In June 2014mentioning
confidence: 99%
“…This is a burning issue that has been studied in the context of employed [19][20][21] and volunteer 28,29 physicians. As noted by Clary and Snyder 36 and documented by Ahmed and Maurana 28 and Shuman et al, 29 recruitment and retention should match the functions that volunteering serves for the volunteer population.…”
Section: Resultsmentioning
confidence: 99%
“…Physicians employed directly by community clinics experience many of the same challenges facing volunteers, leading to similar difficulties in recruitment and retention. [16][17][18][19][20][21] Many studies have focused on how to recruit and retain employed physicians in community clinics. 16,[18][19][20][21] One way is to tailor such programs to the physicians' motivations for working with the underserved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation